4D analysis of malaria parasite invasion offers insights into erythrocyte membrane remodeling and parasitophorous vacuole formation - Niall D. Geoghegan (Nature Portfolio, 2021)
Here, Geoghegan, Evelyn et al. provide a lattice light-sheet microscopy based 4D imaging pipeline to quantitatively investigate Plasmodium spp. invasion and show that the nascent parasitophorous vacuole is predominantly formed from host’s erythrocyte membrane and undergoes continuous remodeling throughout invasion.